Targeting NAD+ metabolism: dual roles in cancer treatment - Yong, Jiaxin; Cai, Songqing; Zeng, Zhaolei (Frontiers in Immunology, 2023)
Nicotinamide adenine dinucleotide (NAD + ) is indispensable for various oxidationreduction reactions in mammalian cells, particularly during energy production. Malignant cells increase the expression levels of NAD + biosynthesis enzymes for rapid proliferation and biomass production. Furthermore, mounting proof has indicated that NAD-degrading enzymes (NADases) play a role in creating the immunosuppressive tumor microenvironment (TME). Interestingly, both inhibiting NAD + synthesis and targeting NADase have positive implications for cancer treatment. Here we summarize the detrimental outcomes of increased NAD + production, the functions of NAD + metabolic enzymes in creating an immunosuppressive TME, and discuss the progress and clinical translational potential of inhibitors for NAD + synthesis and therapies targeting NADase.